The relationship between the selected organizational factors and staff attraction - Nurin Afiqah, Ahmad Zainuddin (Universiti Malaysia Sarawak (UNIMAS), 2019)
Based on the findings, the selected organizational factor in this study (promotion policy, wages, employer branding, and training) has been shown to have a significant relationship with staff attraction. The purpose of this research is to study the relationship between the selected organizational factors and staff attraction. Based on the previous researchers and news, they have concluded that the four variables have a significant relationship with the staff attraction. This study was conducted at one of the manufacturing industries in Malacca, targeting the middle line of the production workers. The population of this study is 90 respondents and the minimum respondents needed from a given population that was provided by Krejcie (1970) for this study is 73 respondents. The total number of respondents that have been acquired in this study by the researcher is 80 respondents. The pilot study has been carried out and was tested by using the Cronbach's Alpha on each of the variables. The alpha value shown in this study for the wages and promotion policy is more than 0.7 which exhibited acceptable reliability results, while the alpha value of the training, employer branding and staff attraction are more than 0.8 which exhibited good reliability results for this study. Pearson Correlation test was used to identify the strength of responses from the questionnaires that were collected. The correlation value for the promotion policy, wages, employer branding, and training is 0.763, 0.713, 0.772 and 0.789 respectively. According to the rules of thumb about Correlation Coefficient size by Sekaran & Bougie (2010), The value obtained by these four variables falls within the Pearson's correlation range of ±0.61 to ±0.80 which is strong. Moreover, Multiple Linear Regressions Analysis discovered that the most dominant factors of the staff attraction are training. Thus, the HR practitioner and organization should emphasize on the factors that can attract the potential candidates into the organization such as develop various training programme for the employees as the training can also helps in increasing employee's wages, provide opportunities for job promotion and improve the image of organization.